Implementasi Active Knowledge Sharing Untuk Meningkatkan Pemahaman Peserta Didik Pada Mata Pelajaran Pai Di Kelas Xi SMK Al Muttaqin OKU Timur - Muhammad Adzkiyaunnuha; Muhadi (Idaarotul Ulum, 2026)
This study aims to analyze the implementation of the Active Knowledge Sharing strategy in improving students' understanding of Islamic Religious Education (PAI) in 11th grade students at SMK Al Muttaqin, East OKU. The research method used was a quantitative one-group pretest-posttest design, in which students were given treatment in the form of the Active Knowledge Sharing strategy in their learning. The study sample consisted of 23 students who were given the Active Knowledge Sharing strategy. Data were collected through pretests and posttests to measure students' understanding before and after the implementation of the Active Knowledge Sharing learning strategy. The results of this study indicate a significant increase in students' understanding after the implementation of the Active Knowledge Sharing strategy. The average pretest score of 47.74 increased to 60.00 in the posttest. The results of the paired sample t-test showed a significance value of 0.000 (p<0.05), confirming that the implementation of the Active Knowledge Sharing strategy had a significant impact on improving students' understanding. The conclusion of this study is that the Active Knowledge Sharing strategy is effective in improving students' understanding of Islamic Religious Education. The Active Knowledge Sharing strategy enables students to be more active in the learning process through discussions, information sharing, and group work, thus improving their understanding of the material. These findings provide implications for educators in choosing more interactive and participatory learning methods to improve the quality of religious education in schools